Improving interactive teaching strategies: action research with a life skills teacher in Oman - Al Harthy, Ziyana S.; Hussien, Suhailah; Alharthy, Hamoud K. (IIUM Press, 2014)
Considering Oman’s engagement in educational reforms that are aimed at improving the educational system to fit the needs and challenges of globalization and the current emphasis on the application of Interactive Teaching Methods (ITMs), this study sought to explore the experiences of Living Skills teachers in engaging in AR to improve Interactive Teaching Strategies (ITSs). It explores the experience of an Omani Life Skills teacher’s involvement in the participatory process of guided Action Research (AR) to improve her Interactive Teaching Strategies (ITSs). Focus is on how this involvement helped her improve her teaching as well as her views and understandings of Interactive Teaching Methods (ITMs). The findings indicate that the teacher was able to accomplish a good transformation of her understanding in some of Interactive Teaching principles and better application in her teaching while highlighting the barriers to the implementation of AR, such as lack of support, poor resources, and time constraints. These findings are hoped to contribute to efforts for developing better and focused teacher training methods for IT and AR support and implementation in Oman.